An Education System for Growth or Concern of Adolescents - Sahar Arab; Tayebe Ziaei; Nasser Behnampour; Elham Khoori (Kerman University of Medical Sciences, 2019)
Introduction: Adolescence is a more Challenging period than other periods of life. Though academic achievement is a universal concern for all students, but the perception of adolescents about these concerns and its severity is more related to the atmosphere and culture of the society in where students live. Hence, according to the effect of education system on adolescents, this study aimed to determine Educational concerns of high school female students from their own perspective. Method: This quantitative content analysis study was performed on 500 high school female students in Gorgan city. Data were collected using an open-ended question about students' concerns about their daily lives. In total, 482 sheets including adolescents concerns, were analyzed. Results: The findings showed three categories of self (%93.8), significant other (%44.8), and peripheral system (%21.2). In this study, the adolescents' concerns categorized in the three categories that were related to their education system, were discussed. Conclusion: The results of this study showed high concern of adolescents about academic achievement. The current education policies push adolescents into one-dimensional life, without learning skills. The result could lead to bringing up adolescents who have difficulty in shaping their personality, humanity, and creativity, and have not learned the essential skills of life. Therefore, society seems to need corrective changes in the education system.